Late antique images of the Virgin Annunciate spinning : allotting the scarlet and the purple - Gines Taylor, Catherine. (Texts and Studies in Eastern Christianity, 2018)
In Late Antique Images of the Virgin Annunciate Spinning: allotting the scarlet and the purple , Catherine Gines Taylor traces the way early Christians assimilated the symbolism of spinning into images of the Annunciation. Taylor offers an art historical and interdisciplinary look at the earliest images of Mary spinning, underscoring the iconographic model of idealized matronage consistent with lay piety and the cult of Mary. The personal and domestic nature of this motif is evidence toward popular Mariological devotion that preceded the exclusive, semi-divine presentation of the Theotokos , and stands in contrast with traditional ascetic models for Mary.